2018
DOI: 10.1186/s12885-018-4587-z
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β signaling promotes tumor vasculature by enhancing the pericyte-endothelium association

Abstract: BackgroundThe breast cancer microenvironment promotes tumor vascularization through the complex interactions involving tumor-associated fibroblasts (TAFs). Emerging data indicate that TAFs increase production and signaling by TGF-β cytokines, while the role of TGF-β signaling in the regulation of tumor blood vessels is not fully understood. The current study presents evidence that TAFs enhance the organization of tumor blood capillaries, and TGF-β signaling plays an important role in this response.MethodsTumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 48 publications
(61 reference statements)
0
50
0
1
Order By: Relevance
“…Moreover, this study observed TGFBR1 rs10512263 has a predictive value for clinical outcomes of gastric cancer patients. Although the function of rs10512263 remains unclear, TGF-β signaling has been suggested to promote gastric cancer progression by enhancing motility and inducing invasiveness of gastric cancer cell [ 11 ], or by promoting tumor vasculature conformation [ 30 ], which could be partly explained for the predictive role of TGFBR1 rs10512263 in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study observed TGFBR1 rs10512263 has a predictive value for clinical outcomes of gastric cancer patients. Although the function of rs10512263 remains unclear, TGF-β signaling has been suggested to promote gastric cancer progression by enhancing motility and inducing invasiveness of gastric cancer cell [ 11 ], or by promoting tumor vasculature conformation [ 30 ], which could be partly explained for the predictive role of TGFBR1 rs10512263 in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study discovered a novel role of TGF-β by tumor-associated fibroblasts (TAFs) in the organization of tumor blood capillaries. TAFs enhanced vessel coverage by pericytes, which are vascular cells that support capillaries [90]. In this regard, mRNA profiling of miR-520/373 overexpressing metastatic MDA-MB-231 cells elicited a strong downregulation of TGF-β signaling.…”
Section: Mirna-mediated Intravasationmentioning
confidence: 95%
“…The difference in signaling of TGF-βmediated apoptosis indicates that the cellular context is essential for controlling the main pathway in the tumor suppressive effects of TGF-β. The tumor promoting effects of TGF-β such as EMT, invasion, metastasis, and angiogenesis emerge when cancer progresses to a later stage (5,87). The upregulation of miR-106b-25 cluster targets Smad7 to ameliorate the TGF-β signaling that is not generally found in normal tissues is an excellent example of this phenomenon.…”
Section: Tgf-β Signaling In the Development Of Cancersmentioning
confidence: 99%